2021
DOI: 10.3389/fpsyg.2021.715700
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of E-Learning and Emotional Intelligence on Psychological Intentions: Study of Stranded Pakistani Students

Abstract: The COVID-19 pandemic has forced the government to close the educational institutions globally, to contain the infection of the disease, which has affected the academic activities of local and international students significantly. This unexpected shift from offline classes to online learning has created psychological disruption among the students. At that backdrop, this study aims to investigate the influence of e-learning and emotional intelligence (EI) on the study stress, burnout, and performance of Pakista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 87 publications
2
19
0
Order By: Relevance
“…It is quite probable that students who obtained a CGPA between 2.5–3.0 were less satisfied with their academic performance during e-learning, which might associate with emotional signs of stress. Our findings are comparable with the findings of a study that demonstrated that international students studying in universities in China during the COVID-19 pandemic experienced high levels of study stress and burnout during e-learning [ 45 ]. Furthermore, these psychological difficulties negatively associate with academic performance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is quite probable that students who obtained a CGPA between 2.5–3.0 were less satisfied with their academic performance during e-learning, which might associate with emotional signs of stress. Our findings are comparable with the findings of a study that demonstrated that international students studying in universities in China during the COVID-19 pandemic experienced high levels of study stress and burnout during e-learning [ 45 ]. Furthermore, these psychological difficulties negatively associate with academic performance.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the provision of academic advising to students with average academic performance will be useful to prevent its repercussions on their future studies and mental well-being. Keeping in view the previous literature, which supports that emotion management and regulation positively contribute to academic performance [ 45 , 46 , 47 , 48 , 49 ], the authors of this study suggest adaptation of such trainings for students in varied educational settings, including online learning environments.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Another intervention based on the improvement of emotional intelligence through workshops and seminars for university students improved the levels of academic performance, academic engagement, and self-efficacy during confinement. The authors of this intervention suggest the importance of including training in socioemotional education in the university curriculum ( Moreno-Fernández et al, 2020 ); other studies have confirmed that emotional intelligence has an impact on burnout, stress, and academic performance in the development of e-learning confined ( Alam et al, 2021 ). It is relevant to consider emotional skills and academic self-efficacy as psychoeducational variables that may impact the adequate psychosocial functioning of students, that is, with self-perceived psychological well-being as an indicator of mental health ( Ryff et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Szczygieł and Mikolajczak [ 38 ] suggested that the trait of emotional intelligence plays a crucial role in promoting subjective well-being, and its beneficial effect is partially mediated via positive emotion regulation. On the other hand, low emotional intelligence is a predictor of high stress, anxiety, and burnout [ 34 , 36 , 45 ].…”
Section: Introductionmentioning
confidence: 99%